Design of Intelligent Disinfection Doormat System Based on STM32 - Tang, Biyuan; Wang, Xu (International Journal of Advanced AI Applications, 2026)
At present, disinfection at the entrances and exits of public places relies heavily on manual operation. To improve the disinfection efficiency and intelligent level of areas with high-frequency personnel flow, this study adopts a modular design method and a centralized control strategy of the main control chip. Taking the STM32 chip as the system’s core control unit, it integrates a stress sensing module, an alcohol atomization disinfection module, an OLED status display module, a Bluetooth communication module and a buzzer prompt module. The system structure is optimized via modular division and function integration, with reasonable control logic and execution process designed to achieve coordinated and stable operation of each module. Finally, a physical prototype is fabricated and performance tests are conducted. Test results demonstrate that the system offers fast response, stable operation and high disinfection efficiency, enabling automatic induction disinfection. It is suitable for high-traffic public places and exhibits excellent practicality and promotional value.